Vibration Properties of Submerged Sandwich Cylindrical Shell Based on Wave Propagation Approach: Analytical and Experimental Investigation - Guoqiang Guo; Yinglong Zhao; Anbin Yu (Shock and Vibration)
The vibration properties of the submerged sandwich cylindrical shell with a viscoelastic core are investigated in this paper. Considering the acoustic-structure coupling, the analytical model of the submerged sandwich cylindrical shell that can handle three medium conditions including fluid-filled, fluid-loaded, and fluid-filled and -loaded is derived based on the wave propagation approach and the Flügge thin-shell theory. The vibration properties of the sandwich cylindrical shell under different medium and boundary conditions are analyzed, followed by a comparison of the damping effect of the constrained damping layer. Finally, an analysis is conducted on the influence of thicknesses of viscoelastic and constrained layers on vibration spectrum and natural frequency under fluid-filled and -loaded conditions. An experimental platform was established to conduct relevant experiments. Several important conclusions can be drawn.